Efficiency, financial performance, and stock returns of the food and beverage industry: A study on the ASEAN 5 - Tan, Jan Dominique O. (Animo Repository, 2022)
The purpose of this study is to see which of the 5 ASEAN countries; Philippines, Malaysia, Indonesia, Thailand, and Vietnam is performing well by using DEA and panel regression analysis to recognize which has the best stock market returns in relation to efficiency, financial performance, and COVID-19. This study used financial ratios such as debt to equity, return on assets, price to earnings ratio, current ratio, accounts receivable turnover, cash conversion cycle, and working capital turnover, including COVID-19, profit efficiency, and productive efficiency, as the independent variable. The figures consist of 10 companies with available data from 2012-2021 from each of the ASEAN 5 stock market exchanges and disclosures. The study’s findings suggest that Indonesia has the highest profit and productive efficiency, with 62.88% and 72.71%. While Thailand and Malaysia got the lowest efficiencies with 24.38% and 23.85%, 24.33%, and 28.29%. All countries have a strong correlation between the financial ratios and dependent variable, stock returns, excluding only Vietnam, with a fair correlation. Lastly, this study concluded that COVID-19 has a significant impact on stock returns in the Food and Beverage Industry in the ASEAN 5.